2015
DOI: 10.1038/srep10886
|View full text |Cite
|
Sign up to set email alerts
|

Surface Curvature Relation to Protein Adsorption for Carbon-based Nanomaterials

Abstract: The adsorption of proteins onto carbon-based nanomaterials (CBNs) is dictated by hydrophobic and π-π interactions between aliphatic and aromatic residues and the conjugated CBN surface. Accordingly, protein adsorption is highly sensitive to topological constraints imposed by CBN surface structure; in particular, adsorption capacity is thought to increase as the incident surface curvature decreases. In this work, we couple Molecular Dynamics (MD) simulations with fluorescence spectroscopy experiments to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 58 publications
(64 reference statements)
7
71
0
Order By: Relevance
“…We can clearly see that the protein load on this particles rises between 30 and 70 nm particle size, stays relatively stable in the region of 70-200 nm and then again rises as the particles grow bigger. Such a trend of increased BSA adsorption onto less curved surfaces was also recently shown by experiment and simulation in the case of carbon nanotubes [37]. Rough calculations using as protein size 2 and 4 nm for myoglobin and BSA, respectively, show that on all particle sizes the adsorption is a thick multilayer.…”
Section: Conformational Changes Of Proteinssupporting
confidence: 76%
“…We can clearly see that the protein load on this particles rises between 30 and 70 nm particle size, stays relatively stable in the region of 70-200 nm and then again rises as the particles grow bigger. Such a trend of increased BSA adsorption onto less curved surfaces was also recently shown by experiment and simulation in the case of carbon nanotubes [37]. Rough calculations using as protein size 2 and 4 nm for myoglobin and BSA, respectively, show that on all particle sizes the adsorption is a thick multilayer.…”
Section: Conformational Changes Of Proteinssupporting
confidence: 76%
“…Similarly, Mu et al [13] showed experimentally that lowering the surface curvature of MWCNTs can induce larger protein conformational changes. Increased protein adsorption capacity on carbon-based NM with flatter surfaces was confirmed also by Zuo et al [16] and Gu et al [67]. All these studies on carbon-based NM are consistent also with previous findings on spherical silica NM [47,48] as well as with our CD-spectroscopy results, which showed that CB and GO with a lower surface curvature decreased the α-helical content (and in the case of GO also decreased the content of β-sheets), while MWCNT with a higher surface curvature did not induce this or any other changes in the secondary structure of electric eel AChE.…”
Section: Interaction Of Nm With Bsa and Cholinesterasessupporting
confidence: 52%
“…Namely, the adsorption of proteins onto carbonbased NM is dictated by hydrophobic and π -π interactions between aliphatic and aromatic residues and the conjugated NM surface. Accordingly, protein adsorption is highly sensitive to topological constraints imposed by carbon-based NM surface structure; in particular, adsorption capacity is thought to increase as the incident surface curvature decreases [56] [67].…”
Section: Interaction Of Nm With Bsa and Cholinesterasesmentioning
confidence: 99%
“…In addition, basic residues like arginine played an equally or even stronger role during this process. Furthermore, in another MD study, the dependence on surface curvature was investigated for adsorption of BSA onto CNTs of increasing radius versus a flat graphene sheet, and the results confirmed that protein adsorption capacity is indeed enhanced on flatter surfaces [87]. …”
Section: Bio-corona Formation On Carbon-based Nanomaterialsmentioning
confidence: 95%